Pattern Analysis of the Relationship Profile of Students’ Curiosity and Internalization-Interconnection of Qur’an and Science - Fadly, Wirawan; Sonia, Nur Rahmi (IAIN Ponorogo, 2023)
This study aims to analyze the profile of curiosity and the pattern of linkages of students' curiosity at all levels of Madrasah Ponorogo to the internalization-interconnection of science material with Qur'anic values. This research employed qualitative research with a naturalistic design. The sampling technique was carried out by purposive sampling of seven people spread across every level of education. Data were collected through interviews, observation, and documentation. Then the data was analysed through descriptive quantitative and qualitative. The results of the research on the curiosity profile of students at each level tend to be associated with events in the observed surroundings, develop according to experience and age, can internalize-interconnect the context of natural events with verses of the Qur'an when they have reached the stage of exploring (adventures) and the pattern of linkages between students' curiosity towards the internalization-interconnection of science material with Quranic values creates the ability for Spiritual-Scientific Accommodation due to stimulation in the form of incentives, attention, scientific dogma, and spiritual interpretation.